Union of the Comoros : Sixth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Waiver of a Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses the Union of the Comoros' Sixth Review Under the Three-Year Arrangement Under the Extended Credit Facility (ECF) and Request for Waiver of a Performance Criterion. Performance under the ECF-supported program through end-June was broadly satisfactory. All but one of the performance criteria and all indicative targets for end-June were met. Most structural benchmarks were also met. The authorities are requesting a waiver for the nonobservance of the performance criterion on net credit to the government at end-June 2013. The IMF staff supports this request and recommends completion of the sixth and final review under the ECF arrangement.